Patients with Barrett's esophagus are hypersensitive to acid but hyposensitive to other stimuli compared with healthy controls. Issue 4 (27th November 2016) - Lottrup, C.; Krarup, A. L.; Gregersen, H.; Ejstrud, P.; Drewes, A. M.
Abstract: Background: Esophageal hyposensitivity has been observed in Barrett's esophagus and may contribute to its pathophysiology. However, studies are few, in particular those assessing different sensory modalities. We aimed to compare esophageal sensitivity to multimodal stimulation in patients with Barrett's esophagus and in healthy controls. Methods: Twenty‐three patients with Barrett's esophagus and 12 healthy controls were examined. A multimodal probe was placed in the lower esophagus. Mechanical, thermal, and electrical stimulation was applied followed by an acid perfusion test with 0.1 N hydrochloric acid. Key Results: Compared with controls, patients were hyposensitive to mechanical distension, heat, and electrical stimulation (all P <.05), but hypersensitive to acid (mean tolerated acid volume 57% lower, P =.001). A linear correlation between acid hypersensitivity and lower baseline impedance was found ( P <.001). Patients had longer esophageal acid exposure time than controls (median acid exposure time 18 vs 5%, P =.03). Asymptomatic patients (no reflux symptoms at baseline) were hyposensitive to mechanical distension, electrical stimulation, and acid perfusion (all P <.05) compared with symptomatic patients. Conclusions & Inferences: Patients with Barrett's esophagus exhibited acid hypersensitivity but hyposensitivity to other stimuli. Lower mucosal baseline impedance, a likely surrogate marker for impaired mucosal integrity, may explain the selective hypersensitivity to acid. On the other hand, the concurrent hyposensitivity may theoretically be explained by changes in central pain modulation. Patients with Barrett's esophagus seem to compose symptomatic and asymptomatic subgroups, showing different esophageal sensory profiles. Abstract : We assessed esophageal sensitivity including mechanical, heat, electrical, and acid stimulation in 23 patients with Barrett's esophagus and 12 controls using the multimodal probe. Patients showed hypersensitivity to acid, but hyposensitivity to other stimuli, asymptomatic patients were generally hyposensitive compared to symptomatic patients, and acid sensitivity overall increased with lower mucosal baseline impedance. We suggest that impaired mucosal sensitivity as measured by the proxy baseline impedance explains the acid hypersensitivity and hypothesize central pain modulation to cause the hyposensitivity to other stimuli.